Review: Attachment and attachment‐related outcomes in preschool children – a review of recent evidence. Issue 1 (25th November 2015) - Barlow, Jane; Schrader‐McMillan, Anita; Axford, Nick; Wrigley, Zoe; Sonthalia, Shreya; Wilkinson, Tom; Rawsthorn, Michaela; Toft, Alex; Coad, Jane
Abstract : Background: Secure attachment is associated with optimal outcomes across all domains in childhood, and both insecure and disorganised attachment are associated with a range of later psychopathologies. Insecure and disorganised attachment are common, particularly in disadvantaged populations, pointing to the need to identify effective methods of addressing such problems. Aims: This paper presents the findings of a review of secondary and primary studies evaluating the effectiveness of interventions aimed at improving attachment and attachment‐related outcomes on a universal, targeted or indicated basis, which was undertaken as part of an update of the evidence base for a UK‐based national programme targeting children aged 0–5 years (Healthy Child Programme). Method: A systematic search of key electronic databases was undertaken to identify secondary and primary sources of data that addressed the research question and that had been published between 2008 and 2014; search sources included Cochrane Collaboration, NICE, EPPI Centre, Campbell Collaboration and PubMed, PsychInfo, CINAHL databases. Findings: Six systematic reviews and 11 randomised controlled trials were identified that had evaluated the effectiveness of universal, selective or indicated interventions aimed at improving attachment and attachment‐related outcomes in children aged 0–5 years. Potentially effective methods of improving infant attachment include parent–infant psychotherapy, video feedback and mentalisation‐based programmes. Methods that appear to be effective in improving attachment‐related outcomes include home visiting and parenting programmes. Conclusions: A number of methods of working to promote attachment and attachment‐related outcomes in preschool children are now being recommended as part of the Healthy Child Programme. The implications in terms of the role and contribution of practitioners working in child and adolescent mental health service are discussed.